Efektivitas Penggunaan Buku Siswa Pelajaran IPA Terpadu Model Sequenced dengan Tema Sistem Adapatasi Tubuh Manusia Pada Suhu Terhadap Aspek Keterampilan Peserta didik SMPN 8 Padang - Asri Devialita; Gusnedi Gusnedi; Ratnawulan Ratnawulan (PILLAR OF PHYSICS EDUCATION, 2018)
The science learning in curiculum, 2013, developed as integrative science. Wherever integrated by physic, biology, and chemistry subject. The real conditions in school that the integrated sciences subject is low. One solution can be done is to apply the integrated science text book sequenced model wich theme adaptation system of human body at temperature. The purpose of study is to investigate the influence of thect booj sequenced Model. Theme adaptation system of human body at temperature toward learning outcomes of students in SMPN 8 Padang.The type of this strudy is Quasi experiment with design Rendomize control-Group design. The population of this study are all of students grade VII in SMPN 8 Padang listed in the school on 2017/2018. Sampling of this study is purposive sampling, the sample in this study are grad VII A as experiment class and grade VIIB as control class all total 64 students. The instrument of study are asheet of learning out comes to assess the aspect of knowledge and asheet of performance to assess the aspect of skill. The data of this study were analysed by using analysist descriptive, hypotesis test, simple linear regression and correlation test.  On the level of real on 0,05 for both aspect. The result of study has be gotten the data knowledge and skills. Result of data analysist that the Text book integrated science subject sequenced model theme adaptation system of human body at temperature give a meaningful effect on learning outcomes onknowladge aspect and skill aspect grad VII on the level of trust 95% the effect of outcomes Skill  student is 17% and 72% affected by other factor.